Bidirectional controller supported inductively coupled dual buck converter based DSTATCOM with passive filterfor PQ improvement - Mangaraj, Mrutyunjaya; Thakur, Rohan Vijay; Mishra, Sanjay Kumar (Institute of Advanced Engineering and Science, 2023)
This research paper explains about the bidirectional controller (BC) supported inductively coupled dual buck converter (IC-DBC) based distributed static compensator (DSTATCOM) with passive filter (PF) for 3-ф 3-wire (3P3W) power distribution system (PDS). The most significant concern in the PDS is power quality (PQ) control. Hence, innovative approach is proposed by considering concept and benefits of BC, inductive coupled filtering transformer (IFCT), passive filter and dual buck converter. Equivalent circuit for IC-DBC based DSTATCOM is realized in view of impedance of transformer and direct coupled dual buck converter (DC-DBC) based DSTATCOM to disclose the filtering mechanism. The supremacy of the proposed DSTATCOM is introduced by comparing its simulation outcomes with DC-DBC based DSTATCOM and IC-DBC based DSTATCOM in terms of better harmonics curtailment, power factor advancement, load balancing & reduced DC link voltage compared to other approaches as per IEEE standard.